1986
DOI: 10.1111/j.1365-2265.1986.tb03626.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin Gene‐related Peptide and Calcitonin in Medullary Thyroid Carcinoma

Abstract: We have investigated the levels of serum calcitonin and calcitonin-gene related peptide (CGRP) in 35 patients with well-documented medullary thyroid carcinoma (MTC). Immunohistochemical investigations for calcitonin and CGRP have been performed on tumour tissue from 9 patients to clarify the cellular pattern of production. In four patients with aggressive disease, serum calcitonin and CGRP values have been monitored in relation to progression of disease after surgery. All 35 patients with MTC have elevated cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

1987
1987
1999
1999

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 23 publications
0
16
1
Order By: Relevance
“…Immunohistochemical localization studies demonstrate CGRP-containing nerve fibers in the central nervous system (33), in nerve fibers throughout the cardiovascular system (35), and in some cells in the thyroid (36) and pancreatic islets (37). However, the similarity of DAP to CGRP raises the possibility that immunohistochemical identification of CGRP in the pancreas may in fact be due to detection of crossreacting determinants on DAP (25).…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical localization studies demonstrate CGRP-containing nerve fibers in the central nervous system (33), in nerve fibers throughout the cardiovascular system (35), and in some cells in the thyroid (36) and pancreatic islets (37). However, the similarity of DAP to CGRP raises the possibility that immunohistochemical identification of CGRP in the pancreas may in fact be due to detection of crossreacting determinants on DAP (25).…”
Section: Discussionmentioning
confidence: 99%
“…Immunocytochemical analysis has localised CGRP in the rat in discrete regions of the central nervous system (Skofitsch & Jacobowitz, 1985a, b) and at nerve endings within the vasculature and heart (Mulderry et al, 1985;Sigrist et al, 1986). In man CGRP has been localised with calcitonin producing cells in the thyroid (Schifter et al, 1986), circulates at low levels in normal plasma (Girgis et al, 1985), and at elevated levels in plasma of patients with lung and medullary thyroid carcinoma (Girgis et al, 1985;Edbrooke et al, 1985). Rat and human have been shown in animal models to be potent inhibitors of gastric acid secretion (Lenz et al, 1985), potent vasodilators (Brain etal., 1985;Holman et al, 1986;Marshall et al, 1986b, c), and can modulate neurotransmission (Al-Kazwini et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…also detected high basal levels of calcitonin gene-related peptide in 26 of 35 patients with medullary thyroid carcinoma, using a radioimmunoassay system with aprotiniü. They observed significantly higher circulating levels of calcitonin than those of calcitonin gene-related peptide in these patients, but they also observed that the ratio of the two peptides varied from patient to patient and that only a small number of eells in tumoürs were stained by änti-cälcitonin geöe-related peptide antibody (21). However, in our study, äl-though the basal level of calcitonin gene-related peptide was high in oüe medullary thyröid carcinoma patient, the mean level in medullary thyroid carcinoma patients was not significantly different ffom that of normal controls.…”
Section: Discussionmentioning
confidence: 89%